The Impact of Earnings Management on Stock Returns with the Moderating Role of Audit Quality in Emerging Markets - Anh, Pham Thi Lan; Hung, Dang Ngoc (International Journal of Economics and Financial Issues, 2025)
This study aims to evaluate the impact of earnings management (EM) on stock returns in the context of emerging markets, while also examining the moderating role of audit quality, represented by the presence of Big 4 audit firms. Utilizing prominent EM measurement models, including Jones (1991), Dechow et al. (1995), and Kothari et al. (2005), the research conducts panel data analysis with firm- and year-fixed effects, along with robustness checks through clustered standard errors. The empirical results reveal a positive association between EM and stock returns, suggesting that earnings management behaviors may be positively received by the market in the short term. However, when audit quality is high (Big 4 auditors), this relationship weakens or even reverses, implying that high-quality audits can mitigate the influence of earnings management activities. Furthermore, the findings indicate a notable difference between listed and unlisted firms, highlighting the role of market monitoring environments. The study contributes to the enrichment of agency theory, signaling theory, and asymmetric information theory in the context of emerging economies.